Postcard - Auteur inconnu (Wikimedia Commons, 1914)
Notice image issue de Wikimedia Commons. Titre: Postcard. Embroidered card, WW1- Home Sweet Home, with Wales ribbon and 3 gift tags, sent by Rifleman 25-1840 Frank S Whitaker, NZRB, to his son, 14 November 1916 'Somewhere in France' embossed card surround printed as postcard verso | embroidered insert with pocket | embroidered message- "HOME SWEET HOME" and illustration of blue bird and village scene | makers details printed verso- "Fabrication française, C.C., Vise Paris"
Licence CC BY 4.0 via Wikimedia Commons
Keywords: carte postale; image; patrimoine; architecture; histoire locale